Information and communications technology initiatives in secondary schools in Trinidad and Tobago - Phillip, Gerard (School of Education, UWI, St. Augustine, 2008)
The education system of Trinidad and Tobago must keep step with international advancements in Information and Communications Technology (ICT). The knowledge-based, technology-driven global environment demands that our education system produce citizens with the ICT skills and competencies to successfully deal with the imperatives of globalization. In order to meet this challenge, teachers and administrative staff must be adequately trained and be disposed to the incorporation of ICT in their delivery of instruction and in the automation of administrative tasks. This paper gives an historical account and a critical analysis of ICT initiatives in the curriculum of secondary schools in Trinidad and Tobago. The paper discusses the findings of a study that investigated the proclivity of teachers and administrative staff of an urban secondary school to the implementation of computer-based technology solutions. The findings showed that many educators are willing to utilize ICT, but most are not trained to use the technology. As a result, costly equipment supplied to schools is left unused or underutilized
Keywords: Information technology; Communication technology; Secondary schools; Trinidad and Tobago